Extracellular microRNAs: key players to explore the outcomes of in vitro fertilization - Haroon Latif Khan; Shahzad Bhatti; Sana Abbas; Celal Kaloglu; Ahmed M. Isa; Hooria Younas; Rachel Ziders; Yousaf Latif Khan; Zahira Hassan; Bilgün Oztürk Turhan; Aysegul Yildiz; Hikmet Hakan Aydin; et al. (BMC, 2021)
Abstract Background MicroRNAs (miRNAs) are small RNA molecules that modulate post-transcriptional gene regulation. They are often used as promising non-invasive biomarkers for the early diagnosis of cancer. However, their roles in assisted reproduction are still unknown. Methods This prospective study was designed to evaluate the expression profiles of seven extracellular miRNAs (miR-7-5p, miR-202-5p, miR-378-3p, miR-224, miR-320a, miR-212-3p, and miR-21-5p) in human follicular fluid (FF) to explore the outcomes of in vitro fertilization (IVF). Of 255 women, 145 were without polycystic ovary syndrome (PCOS), and their ovarian assets were normal (NOR), while 110 were with normo-androgenic PCOS. Results The combination of six FF miRNAs expression profile discriminated between PCOS and NOR women with a sensitivity of 79.2% and a specificity of 87.32% (AUC = 0.881 [0.61; 0.92], p = 0.001). MiR-202-5p significantly had a lower abundance level, and miR-378-3p had a high abundance level in pooled FF samples from patients treated with human menopausal gonadotropin (hMG) than those treated with recombinant follicle-stimulating hormone (rFSH) (p < 0.001). Our results showed that miRNA-320a was significantly different in top-quality embryos versus non-top-quality embryos on day 3 in NOR patients with a sensitivity of 80% and specificity of 71%, (AUC = [0.753 (0.651; 0.855)], p = 0.001). For clinical pregnancy outcome prediction, FF miRNA-21 exhibited high sensitivity (74.8%) and specificity (83.7%) with the AUC value of 0.774 (0.682; 0.865). Conclusion Conclusively, our results provide evidence that miR-7-5p, miR-378-3p, miR-224, miR-212-3p were a differentially high expression in normo-androgenic PCOS patients than NOR patients. While miRNA-320a was significantly different in top-quality embryos versus non-top-quality embryos on day 3 (p = 0.001). The expression level of FF miR-212-3p was significantly related to the probability of embryos to develop into a high-quality blastocyst in patients with normal ovarian reserve.